Emu oil-based lotion effects on neonatal skin barrier during transition from intrauterine to extrauterine life - Zanardo V; Giarrizzo D; Volpe F; Giliberti L; Straface G (Dove Medical Press, 2017)
Vincenzo Zanardo,1 David Giarrizzo,2 Francesca Volpe,1 Lara Giliberti,1 Gianluca Straface1 1Division of Perinatal Medicine, Policlinico Abano Terme, Abano Terme, 2CALANTHA Physiology of Lactation Laboratory, Padua, Italy Abstract: Both appropriate hydration and skin surface pH are fundamental in preventing baby skin barrier damage during transition from intrauterine to extrauterine life. However, effects of topical moisturizers on neonatal stratum corneum temperature, pH, hydration, and elasticity have not been scientifically evaluated in vivo. We checked 31 full-term breastfeeding neonates by non-invasive bioengineering method, which is able to evaluate the basal skin barrier (left heel), and assessed at 6±1 hours after birth, and at 1 and 24 hours after emu oil-based topical treatment. The basal skin barrier of right heel (no oil exposure) of each newborn was considered as control. We found that a single application of an emu oil-based lotion was effective in improving heel stratum corneum hydration, which increases both skin pH and elasticity without any effect on temperature. Further studies are needed to confirm long-term beneficial effects of this treatment in a very sensitive patient population. Keywords: skin barrier, neonate, emu oil-based lotion, topical treatment